STRATEGI OPTIMALISASI PENGELOLAAN DANA PERIMBANGAN DI INDONESIA - Nurkhayat, Ahmad; Firdaus, Muhammad; MUlatsih, Sri (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2018)
ABSTRACTBalanced Fund is a part of the fund transfers by the central government to the regional government in implementing fiscal decentralization. The aims of this policy are to: (1) reduce the inequality of funding sources between central and regional governments (vertical imbalance), and the inter-regional imbalance (horizontal imbalance), (2) reduce public service gap among regions. The objectives of this study are to (1) describe the implementation of Balanced Fund in Indonesia, (2) analyze the effects of Balanced Fund on economic growth, (3) formulate optimization strategy of Balanced Fund management in Indonesia. This study used descriptive analysis,panel data regression analysis, and SWOT analysis. Descriptive analysis indicates that Balanced Fund has not been able to optimize equitable regional distribution of financial capability, particularly for regencies and cities. Panel data regression analysis shows that General Allocation Fund and Special Allocation Fund have positive effects on economic growth, except in Banten in which Special Allocation Fund has no effects. Meanwhile, Revenue Sharing Fund results in negative effects on economic growth, except in East Java in which it has no effects. SWOT analysis formulates eight alternative strategies which may be implemented by the Central Government in optimizing the Balanced Fund management.Keywords: General Allocation Fund, panel data, Revenue Sharing Fund, Special Allocation Fund, SWOTABSTRAKDana Perimbangan merupakan bagian dari dana transfer Pemerintah Pusat kepada PemerintahDaerah. Dana ini bertujuan:(1) mengurangi ketimpangan sumber pendanaan antara pusat dan daerah (vertical imbalance), dan ketimpangan antar daerah (horizontal imbalance), dan (2) mengurangi kesenjangan layanan publik antar daerah. Tujuan dari penelitian ini adalah (1) mendeskripsikan implementasi Dana Perimbangan di Indonesia, (2) menganalisis pengaruh Dana Perimbangan terhadap pertumbuhan ekonomi, dan (3) merumuskan strategi optimalisasi pengelolaan Dana Perimbangan di Indonesia. Penelitian ini menggunakan analisa deskriptif, analisis regresi data panel, dan analisis SWOT. Analisis deskriptif menunjukkan bahwa Dana Perimbangan belum sepenuhnya mampu menciptakan pemerataan kemampuan keuangan daerah terutama untuk wilayah kabupaten dan kota. Analisis regresi data panel digunakan untuk menganalisis pengaruh Dana Perimbangan terhadap pertumbuhan ekonomi provinsi-provinsi di Indonesia. Analisis ini menunjukkan bahwa DAU dan DAK memiliki pengaruh positif terhadap pertumbuhan ekonomi, dan DBH berpengaruh negatif. Hasil analisis SWOT merumuskan delapan alternatif strategi yang dapat dilaksanakan oleh Pemerintah Pusat dalam rangka optimalisasi pengelolaan Dana Perimbangan.Kata kunci : Dana Alokasi Umum, data panel, Dana Revenue Sharing, Dana Alokasi Khusus, SWOT